Political violence in Southeast Asia since 1945
1 online resource (xix, 308 pages)
Keywords: "This book examines postwar waves of political violence that affected six Southeast Asian countries-Indonesia, Burma/Myanmar, Cambodia, Thailand, the Philippines, and Vietnam-from the wars of independence in the mid-20th century to the recent Rohingya genocide. Featuring cases not previously explored, and offering fresh insights into more familiar cases, the chapters cover topics including the technologies of violence, the politics of fear, inclusion and exclusion, justice and ethics, repetitions of mass violence events, impunity, law, ethnic and racial killings, crimes against humanity, and genocide. The book raises key questions for the study of mass violence worldwide"--